Hyperspectral imaging applications in rapeseed and mustard farming: HYPERSPECTRAL IMAGING APPLICATIONS IN RAPESEED AND MUSTARD FARMING - ABHINAV KUMAR; VANDANA BHARTI; VINOD KUMAR; P D MEENA; G SURESH (Journal of Oilseeds Research, 2017)
Hyperspectral Imaging (HSI) technology provides incomparable capabilities for detection of physical, chemical, and biological properties of the samples, which is not possible with either spectroscopy or imaging alone. In agriculture, this technique is quite useful for monitoring the agricultural situation, retrieval of biophysical parameters and management/decision support for agricultural development. The applications of the technique are of considerable importance for macronutrient analysis of plants including mapping of foliar nitrogen, detection of nitrogen deficiency, visualization of chemical distribution in leaves etc. For rapeseed and mustard farming, the technology has been found to be fairly useful for the detection of different pathogens and disease prognosticating, detection of pests and monitoring damages due to infestation, macronutrient analysis for monitoring fertilizer application, mapping of weeds population, prediction of seed yield, and determination of oilseed planting area.